Facile synthesis of 2-(2-aminobenzoyl)benzoic acids via a base-promoted aerobic cascade reaction. Issue 9 (13th March 2019) - Shen, Jinhai; Chen, Yangxin; Chen, Ting; Zou, Zhongai; Feng, Yadong; You, Qihua
Abstract : A novel base-promoted aerobic cascade reaction for the regiospecific synthesis of 2-(2-aminobenzoyl)benzoic acids under metal-free conditions is developed. Abstract : A novel strategy for the regiospecific synthesis of 2-(2-aminobenzoyl)benzoic acids via a base-promoted aerobic cascade reaction has been exploited. The protocol led to a wide panel of 2-(2-aminobenzoyl)benzoic acids with a broad substrate scope in an atom-economical manner. Six new bonds were sequentially formed in this one-pot procedure.